JARAK DAN VOLUME UPPER AIRWAY PADA PASIEN PASCA OPERASI PALATOPLASTY MENGGUNAKAN CONE BEAM COMPUTED TOMOGRAPHY (CBCT) - Fitriana; Yulia, Dhafina Gita (E-Prodenta Journal of Dentistry, 2025)
Introduction: Cleft lip and palate (CLP) is a congenital anomaly with a global incidence of 1/500–1/1000 births, reaching 7,500 cases per year in Indonesia (Riskesdas 2019). Palatoplasty, a reconstructive procedure of the palate to restore velopharyngeal and speech function, is typically performed at 1–1.5 years of age in Indonesia. This study uses CBCT a low-radiation 3D radiology tool to analyze changes in upper airway distance and volume post-palatoplasty, as no similar studies have been conducted in Indonesia (particularly in Malang) to evaluate the anatomical impact of the surgery on the airway, obstruction risk, and patient quality of life. Objective: To observe and measure the distance and volume of the upper airway in CLP and/or CP patients after palatoplasty using CBCT. Methods: A cross-sectional study to observe and measure the condition of the upper airway in patients who have undergone palatoplasty, measured using CBCT. Results: CLP patients after palatoplasty generally have a wider airway and larger volume compared to normal individuals. Widening of the airway generally improves respiratory function, reduces the risk of sleep apnea, and enhances airflow. However, if narrowing occurs at specific points (e.g.,low PASmin), the risk of respiratory disorders such as OSA remains. Conclusion: CBCT is highly accurate in measuring the distance and volume of the airway in three dimensions.